The correlation of full-day school on student academic stress - M. Fatchurahman (Jurnal Konseling dan Pendidikan, 2021)
The research base on the education system's phenomenon in Indonesia implements full-day school, which triggers academic stress experienced by students in schools, particularly in Central Kalimantan. This study aimed to get empirical data on a significant effect of a full-day school on academic stress. Statistical data analysis in this study using simple linear regression analysis. The sample in this study was 53 students who were taken by purposive sampling. The Likert scale uses as an instrument for collecting data related to academic stress. The full-day school does not affect students' academic stress. Evidenced by the results of the Pearson analysis, which shows that the value of the t count is 0.379 while the value of the T table is 0.679. Pearson analysis shows that T count is less than T table so that it can see that there is no relationship between full-day school and student academic stress. The results of the study indicate that the school can still carry out full day learning for its students but still pay attention to psychological conditions so that learning outcomes remain quality. the school needs to develop special policies related to full day school so that learning is carried out in accordance with the flow of the existing education system.